A multicenter, epidemiological study of the treatment patterns, comorbidities and hypoglycemia events of patients with type 2 diabetes and moderate or severe chronic kidney disease – the 'LEARN' study. (3rd May 2016) - Rombopoulos, Grigorios; Panitti, Elena; Varounis, Christos; Katsinas, Christos; Stefanidis, Ioannis; Goumenos, Dimitrios
Abstract: Objective Management of patients with type 2 diabetes (T2DM) and stage 3 to 5 chronic kidney disease (CKD) is challenging. The aim of the 'LEARN' study was to describe treatment patterns employed in this population and to record comorbidities, glycemic control and hypoglycemia episodes in routine clinical practice in Greece. Research design and methods 'LEARN' was a non-interventional, multicenter, cross-sectional study conducted in Greece between 15 February 2013 and 4 July 2013. A total of 120 adult patients were enrolled from four hospital sites in different geographic regions of Greece. Results Participants had a mean age of 69.1 ± 10.3 years and a male:female ratio of 2:1. Nearly all patients (99.2%) suffered from at least one comorbidity, with hypertension (95.8%) and hyperlipidemia/dyslipidemia (78.3%) being the most prevalent. Of the overall study population, 57.5% was managed with insulin therapy only, 30.8% with oral antidiabetics only and 11.7% with a combination of insulin and oral antidiabetics. The overall rate of glycemic control, defined as glycated hemoglobin (HbA1c ) ≤ 7.0% during the most recent assessment, was 55.0%. This rate was significantly higher among those receiving oral antidiabetics only (73.0%) compared to insulin only (47.8%) or a combination of both types of treatment (42.9%) ( p  = 0.03). Moreover, patients receiving oral antidiabetics only had experienced fewer hypoglycemia episodes over the last 7 days prior to the study visit (0.1 ± 0.4) compared to patients receiving insulin only (0.9 ± 1.7) ( p  = 0.03). Conclusions Although this is an observational study, it seems that oral antidiabetic therapy might be advantageous for heavily burdened T2DM patients with moderate or severe CKD in terms of glycemic control and hypoglycemia episodes. More data preferably from randomized trials is needed in order to validate this hypothesis.